”Jag ville testa på att plugga på universitetet… och så ville jag få jobba med barn” - Live Stretmo (Educare)
During the past two decades, teacher education has come to comprise the largest student enrollment in higher education programs in the Swedish context. This study examines 11 students enrolled in a teacher program specializing in school-age educare (grundlärare i fritidshem). School-age educare students exhibit a notable gender balance and many come from low-level educational and/or migrant backgrounds, leading to an exploration into the (re)production of class and gender dynamics. Through a thematic analysis of interviews, this article delves into how these students articulate their educational choices in relation to migrant background, gender, and class, and envision their future profession. The study highlights the dual motivation driving their specific educational decision: a desire for higher education and the need to enhance employability. Within this context, school-age educare emerges as a distinct and special kind of teacher endeavor. Gender, as perceived by the students, could both be framed as an asset and as a possible obstacle in discussions about their future profession. Male teachers could be both viewed as important role models yet also as ambivalent figures. This study offers insights into the interplay of class, gender, migrant background and educational aspirations, contributing to a more nuanced understanding of contemporary teacher education in Sweden.